On Uzbek Television Interpretation Of The Neighborhood Theme: Approach, Format And Style Issues (Zien Journal of Social Sciences and Humanities, 2024)
In this article, we cannot deny that in today's era of globalization, the media, like all spheres, are developing with new views and trends, and while the rating of modernity and nonconformity is one of the main features for loud, popular programs, elements of nationalism and tradition are certainly present in any media product. In this respect, the article explores the neighborhood's coverage on television, their own traditional and national characteristics.